Locke & key (2008), volume 6 ebook Alpha & omega. - Hill, Joe (Locke & Key (2008), 2014)
The shadows have never been darker and the end has never been closer. Turn the key and open the last door; it's time to say goodbye. Omega and Alpha, the final two storylines of the New York Times bestselling series, are collected together to offer a thunderous and compelling conclusion to Locke & Key. An event not to be missed! Author: Joe Hill. Illustrator: Gabriel Rodriguez. Locke & Key script © 2019 Joe Hill; art © 2019 Idea and Design Works, LLC. All Rights Reserved.